Gender and Food Security in Nigeria: the Role of Corporate Social Responsibility in the Oil Producing Communities - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2023)
The purpose of this paper is to critically examine the multinational oil companies' (MOCs) corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of the global memorandum of understanding (GMoU) on gender and food security in the Niger Delta region of Nigeria. This paper adopts a survey research technique aimed at gathering information from a representative sample of the population. A total of 800 women respondents were sampled across the rural areas of the Niger Delta region. It is essentially cross-sectional: describing and interpreting the current situation. The results from the use of a combined propensity score matching (PSM) and logit model indicate that CSR interventions of the MOCs using GMoUs have contributed in empowering women to effectively discharge their role in food and nutritional security. This is achieved by enhancing coherence in policies on gender, agriculture, nutrition, health, trade and other relevant areas in the Niger Delta. The findings also show that CSR intervention of MOCs supported ecological sound approaches to food production, such as agro-ecology that promotes sustainable farming and women's empowerment in the region. This suggests that recognizing and respecting the local knowledge of farmers, including women farmers, will help develop locally relevant food and nutrition security in sub-Saharan Africa. This implies that promoting the implementation of everybody's right to food, particular that of women, as well as giving women rights to other resources like land, in addition to engaging women and men in challenging the inequitable distribution of food within the household will help strengthen food security in Africa. This research contributes to the gender debate in agriculture from a CSR perspective in developing countries and serves as a basis for the host communities to demand for social projects. It concludes that corporate establishments have an obligation to help in solving problems of public concern.
Keywords: 330; Gender; food security; corporate social responsibility; multinational oil companies; sub-Saharan Africa